Exploring Japanese nurses’ perceptions of the relevance and use of assertive communication in healthcare: A qualitative study informed by the Theory of Planned Behaviour - Mieko Omura (2018)
© 2018 Elsevier Ltd Background: The hierarchical nature of healthcare environments presents a key risk factor for effective interprofessional communication. Power differentials evident in traditional healthcare cultures can make it difficult for healthcare professionals to raise concerns and be assertive when they have concerns about patient safety. This issue is of particular concern in Japan where inherent cultural and social norms discourage assertive communication. Aim: The aim of this study was to (a) explore nurses’ perceptions of the relevance and use of assertive communication in Japanese healthcare environments; and (b) identify the factors that facilitate or impede assertive communication by Japanese nurses. Design: A belief elicitation qualitative study informed by the Theory of Planned Behaviour was conducted and reported according to the COnsolidated criteria for REporting Qualitative research. Settings and Participants: Twenty-three practicing Japanese registered nurses were recruited by snowball sampling from October 2016 to January 2017. Methods: Individual face-to-face semi-structured interviews were conducted and transcribed in Japanese and then translated into English. Two researchers independently conducted a directed content analysis informed by the Theory of Planned Behaviour. Participants’ responses were labelled in order of frequency for behavioural beliefs about the consequences of assertive communication, sources of social pressure, and factors that facilitate or impede assertive communication in Japanese healthcare environments. Findings: Although person-centred care and patient advocacy were core values for many of the participants, strict hierarchies, age-based seniority, and concerns about offending a colleague or causing team disharmony impeded their use of assertive communication. Novice nurses were particularly reluctant to speak up because of their perception of having limited knowledge and experience. Conclusion: This study identified Japanese nurses’ behavioural, normative, and control beliefs in relation to assertive communication. The findings will be used to inform the development of a culturally appropriate assertiveness communication training program for Japanese nurses and nursing students.